Ethical Sensitivity: State of Knowledge and Needs for Further Research - Weaver, Kathryn (Nursing ethics, 2007)
Ethical sensitivity was introduced to caring science to describe the first component of decision making in professional practice; that is, recognizing and interpreting the ethical dimension of a care situation. It has since been conceptualized in various ways by scholars of professional disciplines. While all have agreed that ethical sensitivity is vital to practice, there has been no consensus regarding its definition, its characteristics, the conditions needed for it to occur, or the outcomes to professionals and society. The purpose of this article is to explore the meaning of the concept of ethical sensitivity based on a review of the professional literature of selected disciplines. Qualitative content analysis of the many descriptors found within the literature was conducted to enhance understanding of the concept and identify its essential characteristics. Ethical sensitivity is considered to be an emerging concept with potential utility in research and practice.